Conversion of sustained supraventricular tachycardia into sinus rhythm after stellate ganglion block: A case report and pathophysiological considerations - Caroline Chevalier; Lorenz Fischer (Journal of International Medical Research)
Considering the anatomy, physiology, and pathophysiology of the autonomic nervous system of the heart, therapy by means of stellate ganglion block may be a logical additional treatment option in certain cases of heart rhythm disorders. A woman in her late 60s presented with sustained paroxysmal supraventricular tachycardia and a heart rate of 170 beats per minute that had persisted for 2 h despite performing vagal maneuvers and orally administering 40 mg of verapamil. She had a history of several episodes of paroxysmal supraventricular tachycardia with spontaneous conversion. We performed a stellate ganglion block with 3 mL of 1% procaine. One minute later, the paroxysmal supraventricular tachycardia converted into a normal sinus rhythm. Since then (i.e. since 5 years), the patient has not experienced any further episodes of tachycardia. In addition to various other pathomechanisms of paroxysmal supraventricular tachycardia, neuroplastic and neurogenic inflammatory processes play a role, in which the sympathetic nervous system contributes to pathological positive feedback loops. Stellate ganglion block interrupts these feedback loops, allowing the autonomic nervous system to reorganize and achieve a better balance. This could exert a favorable effect on recurrences of heart rhythm disorders (“learning effect”). Stellate ganglion block via local anesthetics is a simple, safe, and virtually side effect-free procedure to terminate treatment-refractory paroxysmal supraventricular tachycardia. Further studies are needed to confirm these results.